2020
DOI: 10.3390/cancers12020490
|View full text |Cite
|
Sign up to set email alerts
|

Stiffer Matrix Accelerates Migration of Hepatocellular Carcinoma Cells through Enhanced Aerobic Glycolysis Via the MAPK-YAP Signaling

Abstract: Increased extracellular matrix (ECM) stiffness and metabolic reprogramming of cancer cells are two fundamental mediators of tumor progression, including hepatocellular carcinoma (HCC). Yet, the correlation between ECM stiffness and excessive aerobic glycolysis in promoting the development of HCC remains unknown. Here, we demonstrated that stiffer ECM promotes HCC cell migration depending on their accelerated aerobic glycolysis. Our results also indicated that stiffer ECM-induced YAP activation plays a major ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 46 publications
2
44
1
Order By: Relevance
“…Previous studies have also shown that stiffness upregulates YAP/TAZ expression in various types of cells ( 24 , 25 , 29 32 ), such as hepatocellular carcinoma ( 25 ), hepatic stellate cells ( 33 ) and pulmonary artery endothelial cells ( 30 ). Consequently, this YAP/TAZ-mediated upregulation promotes uptake and utilization of cellular glucose, increases glycolysis, and influences glycogenolysis.…”
Section: Ecm Stiffness and Glucose Metabolismmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have also shown that stiffness upregulates YAP/TAZ expression in various types of cells ( 24 , 25 , 29 32 ), such as hepatocellular carcinoma ( 25 ), hepatic stellate cells ( 33 ) and pulmonary artery endothelial cells ( 30 ). Consequently, this YAP/TAZ-mediated upregulation promotes uptake and utilization of cellular glucose, increases glycolysis, and influences glycogenolysis.…”
Section: Ecm Stiffness and Glucose Metabolismmentioning
confidence: 98%
“…The mechanisms through which ECM stiffness upregulates YAP/TAZ are diverse, and may be regulated differently across different cell types. Generally, these mechanisms are broadly categorized as: (i) effect on cytoskeletal tension ( 24 ); (ii) effect on hyaluronic acid (HA) receptor CD44 ( 16 ); (iii) activation on the MAPK signaling cascade in hepatic cancer cells ( 25 ); (iv) ECM stiffness can affect cellular metabolism through integrin (discussed in a later section), and it has been reported that integrin affects cellular metabolism through YAP/TAZ ( 26 ). However, it is unclear whether ECM stiffness can activate YAP/TAZ through integrin.…”
Section: Ecm Stiffness and Glucose Metabolismmentioning
confidence: 99%
“…[6][7][8][9] Under physiological circumstances, FREM1 is widely expressed in epithelial-mesenchymal interaction and epidermal remodeling areas, for example, hair follicles, sensory vibrissae, teeth, footpads, and breast tissue. 10 Growing studies have shown that ECM-related proteins may modulate the migration and invasion of cancer cells through related signaling pathways, such as β1-integrin-Src-EGFR, 11 MAPK-YAP, 12 and PI3K-AKT signaling. 13 More importantly, the deposition, reconstruction, and cross-linking of ECM can reprogram the local microenvironment and regulate the pro-and antitumor immune responses upon the stimulation of different ECM-related proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma, induced ECM stiffness activated YAP downstream of c-Jun N-terminal kinases (JNK) and p38. In turn YAP activation increased the glycolytic pathway and migration of cancer cells [ 54 ]. YAP/TAZ has also been found to promote cancer cell proliferation by upregulating deoxynucleotide synthesis and inhibiting RAS-induced senescence in cells.…”
Section: Tumor Cell/caf Interaction-driven Metabolic Rewiring In Cmentioning
confidence: 99%